La representation du divin dans les récits du Pentateuque : mediations syntaxiques et narratives - Mirguet, Françoise, 1980- (Vetus Testamentum, Supplements, 2009)
Though several studies have already been devoted to biblical representations of God, the present research considers the position towards the divine they imply, on the basis of syntactic and narrative analysis. The book examines, in the stories of the Pentateuch, different appearances of the divine character: his speeches, as well as their modes of reporting; his actions, their mediations, and the points of view from which they are told; his perceptions and emotions, as well as the so-called omniscient narration; and some interpretations and distortions of his words. It appears that the Pentateuch presents the divine in an essentially mimetic way, mainly from the perspectives of other characters, portraying different human experiences and interpretations of divinity.